Characteristics of Bleeding Complications in Patients with Severe COVID-19 Requiring Veno-venous Extracorporeal Membrane Oxygenation in Japan - Taniguchi, Hayato; Abe, Takeru; Takeuchi, Ichiro; Ohshimo, Shinichiro; Shime, Nobuaki; Kushimoto, Shigeki; Hashimoto, Satoru; Takeda, Shinhiro; on behalf of the Japan ECMO Network (Thrombosis and Haemostasis, 2024)
Complications during veno-venous extracorporeal membrane oxygenation (VV-ECMO) are associated with in-hospital mortality. Asian patients on extracorporeal membrane oxygenation (ECMO) have higher risks of bleeding and in-hospital mortality than Caucasian patients. This study aimed to characterize and identify bleeding complications and their associated factors related to in-hospital mortality in patients with severe coronavirus disease 2019 (COVID-19) requiring VV-ECMO in Japan.In this retrospective observational analysis, the prospective nationwide multicenter registry was used to track real-time information from intensive care units throughout Japan during the COVID-19 pandemic. VV-ECMO patients' registry data between February 1, 2020 and October 31, 2022 were used.This study included 441 patients; 178 (40%) had bleeding complications in the following sites: 20% at the cannulation site, 16% in the gastrointestinal tract, 16% in the ear–nose–throat, 13% at the tracheostomy site, 9% intrathoracic, 6% intracranial, and 5% in the iliopsoas. Anticoagulation was discontinued in >50% of patients with intracranial, iliopsoas, and gastrointestinal tract bleeding. ECMO was discontinued in one-third of patients with intracranial, intramuscular, and iliopsoas hemorrhages. Multivariable logistic regression analysis revealed that only gastrointestinal tract bleeding was associated with in-hospital mortality (odds ratio: 2.49; 95% confidence interval: 1.11–5.60; p = 0.03).Incidence of bleeding complications was 40% in the Japanese population. Gastrointestinal tract bleeding emerged as a significant predictor of adverse outcomes, necessitating further research into preventive strategies and optimized care protocols. These findings can guide the management of VV-ECMO patients with COVID-19.
Keywords: bleeding; coronavirus disease 2019; gastrointestinal tract; respiratory distress syndrome; mortality